A Clinical Study of Guduchi Tinospora cordifolia Willd Miers ex Hook f Thoms in Antihyperlipidemic Effect w s r to Sthaulya - Khemchand Sharma, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
A Clinical Study of Guduchi Tinospora cordifolia Willd Miers ex Hook f Thoms in Antihyperlipidemic Effect w s r to Sthaulya